The Integration of Sustainable Cities in the Marshes (Iraq). (June 2019) - Rashid Kbah, A A
Abstract: The extensive marshlands of Mesopotamia represent a unique component of our global heritage and resources. The seas of reed beds were home to ancient communities rooted in the dawn of human history. The wetlands are the locale in which human civilization began with the Sumerian culture more than 5, 000 years ago. Scholars regard the marshes as the site of the biblical"Garden of Eden, " the "Great Flood, " and the birthplace of the patriarch Abraham. On the shores of the marshes, the legendary Epic of Gilgamesh was enacted. World-renowned archaeological sites on the fringes of the marshes include Ur, Uruk, Eridu, Larsa, Lagash and Nina.The current marsh dwellers are our only link with this rich cultural past. Following the end of the Gulf War in 1991, the marsh dwellers were important elements in the uprising. To end the rebellion, the regime implemented an intensive system of drainage and water diversion structures that desiccated over 90% of the marshes. The reed beds were also burned and poison introduced to the waters. It is estimated that more than 500, 000 were displaced, 95, 000 of them to Iran, 300, 000 internally displaced, and the remainder to other countries. By January 2003, the majority of the marshes were wastelands. From this point and to re settling the local community the research trying to present a sustainable village in the marshes that can be built from local materials and depend on the local society.